1994
DOI: 10.1002/polb.1994.090320512
|View full text |Cite
|
Sign up to set email alerts
|

The annealing and thermal analysis of poly(butylene terephthalate)

Abstract: When poly(butylene terephthalate) (PBT) is annealed, a second endotherm is often displayed in a subsequent scanning thermal analysis at a temperature below that of the original endotherm, and this new endotherm appears to grow with annealing at the expense of the original. This growth is not due to chemical changes, because the thermogram obtained before annealing is recovered after complete melting. But a physical change would also seem unlikely because the transformation of higher‐melting into lower‐melting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 27 publications
5
54
0
1
Order By: Relevance
“…Wilkinson et al 28 also found the same phenomenon in the PP/PA6/SEBS-g-MA ternary blends and attributed the shoulder peak to the secondary crystallization of PA6 component. [29][30][31] The extruded PA6 used in the study also exhibits this bimodal melting behavior under the same measurement condition. The conditions that reduce the mobility of chain segments after primary crystallization has occurred, such as rapid cooling 28 and crystallization at high degrees of undercooling, 2,28 can suppress the development of the low temperature shoulder and produce a melting endotherm with a single peak.…”
mentioning
confidence: 85%
“…Wilkinson et al 28 also found the same phenomenon in the PP/PA6/SEBS-g-MA ternary blends and attributed the shoulder peak to the secondary crystallization of PA6 component. [29][30][31] The extruded PA6 used in the study also exhibits this bimodal melting behavior under the same measurement condition. The conditions that reduce the mobility of chain segments after primary crystallization has occurred, such as rapid cooling 28 and crystallization at high degrees of undercooling, 2,28 can suppress the development of the low temperature shoulder and produce a melting endotherm with a single peak.…”
mentioning
confidence: 85%
“…Various interpretations and/or explanations on the melting behavior of these semi-crystalline polymers have been proposed. Yeh and Runt, 5 and Robertson et al, 6,7 have shortly summarized the interpretation on the melting behavior of PET and PBT in their articles. Since PBT evidently results in the double melting peaks when observed by a differential scanning calorimeter (DSC), [5][6][7][8][9][10][11] PBT is a suitable polymer for an analysis of the melting behavior of the semi-crystalline polymers.…”
Section: Introductionmentioning
confidence: 97%
“…Many authors [5][6][7] have explained the double melting behavior of PBT by the melt-recrystallization model. In the model, the low-temperature endothermic peak has been explained to represent only a portion of the melting of original crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After injection, all samples passed through an annealing process at 180°C during two hours, in order to erase thermal history and eliminate possible residual stresses arising from the molding process 3,17,18 . For the measurement of initial weight values before aging, the samples were rinsed quickly in acetone, wiped dry with a paper tissue and then immediately weighed using a high precision analytical balance.…”
Section: Preparation Of the Samplesmentioning
confidence: 99%